Perlindungan Konsumen atas Kerusakan/Kehilangan Pakaian Pada Jasa Usaha Laundry di Denpasar - I Komang Dodik Wijaya; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Warmadewa Press, 2021)
Currently increasingly sophisticated technology creates a new rental service such as laundry. Law No. 8 of 1999 on Consumer Protection can be a foundation for consumers and consumer protection agencies to empower and protect consumer interests, and to make business actors more responsible. This research aims to explore legal protection for laundry consumers for damage / loss of goods and to explain the responsibilities of laundry business actors for damage/loss of goods. This study uses empirical legal research. The data sources used are primary and secondary data. Data obtained through interview and documentation techniques then processed and analyzed using qualitative data processing techniques. The results of the research show that consumers who have been harmed by the negligence of the business actor can hold the business actor accountable for him, as well as claim compensation for the losses they have suffered, this is as stated in Article 7 letter G UUPK. The form of accountability of laundry business actors varies between business actors. In the case of giving compensation to consumers, the business actor in accordance with Article 19 of the UUPK must provide compensation not later than 7 days, if it passes the time limit, the consumer can sue the business actor.